Bem viver e marcas culturais tanzanianas: a experiência da AFYA na reconstrução da relação das mulheres com a saúde em territórios de pobreza - Silva, Edna Maria Do Nascimento Da (2019)
This research aims to study the health promotion practices experienced by the Afya- Centro Holístico da Mulher - Non-Governmental Organization formed by women who have developed a health work in the district of Alto do Mateus, since 1998. The aim is to identify the underlying cultural brands in the health promotion practices of the Afya Centro Holístico da Mulher - considering the importance of the practical relationship and theory in health. In the same direction, the interest is to analyze to what extent the Entity's work methodology interweaves elements of its Tanzanian- African origin with the Freirean perspectives. It is interesting to inventory how starts the construction of knowledge in health by the women of the popular classes, protagonists of the Afya. There has also been an effort to identify the current orientations that are present in Afya, based on a perspective of Health from ancestral origins, as expressions of what is explicitly referred to as "living well." The problem that arises: what deep cultural interconnections can be identified in Afya's health promotion practices, which indicate a process of building new forms of health learning and strengthening social struggles? The Participating Research was adopted because it has methodological characteristics of the "Participatory Action Research - IAP", methodology developed by the researcher, sociologist and popular educator, Colombian, Orlando Fals Borda. The thesis proposes to rethink how the educational processes experienced by Afya women, affected by the experience of cultural circularity, mediated by orality, contribute to the transformation of their realities. In this sense, the interlocution between differentiated cultures, such as Tanzanian ancestral African culture, in contact with American culture, with the culture of Paraiba, through practices in popular education in health, holistic therapies, articulated by the promotion of the health of the well live, can trigger a process of reappraisal of the practices and directions of Afya in its twenty years of existence.